Acceptance and perceived usefulness of digital health services in the management of chronic urticaria: a survey of patients and physicians - Michael Hindelang; Alexander Zink; Johannes Knitza; Robert Darkow; Martin Welcker; Tilo Biedermann; Susann May; Felix Muehlensiepen (BMC Health Services Research)
Abstract Background Chronic urticaria (CU) is a complex and unpredictable skin condition that significantly affects patients’ quality of life. As the healthcare landscape increasingly integrates digital health technologies, understanding their perceived usefulness in CU management from both patient and physician perspectives is crucial. Objective This study investigates the acceptance, perceived usefulness, and potential barriers to using digital health services, such as medical apps and video consultations, among patients with CU and their healthcare providers. Methods A quantitative survey was conducted across multiple specialized centers, specialist clinics, and general practices, involving both patients and physicians. The study utilized standardized questionnaires to assess digital health literacy, technology readiness, and attitudes toward adopting digital health services in CU management. Descriptive and inferential statistics, including Fisher’s exact test, were employed to analyze the data. Results A substantial proportion of the 121 surveyed patients and 101 physicians perceived digital health technologies as beneficial in managing CU, with 59.5% of patients and 75.3% of physicians agreeing on their advantages. However, 21.5% of patients and 14.9% of physicians remained neutral, while 8.3% of patients and 4.0% of physicians found these technologies unhelpful. Key barriers to adoption were identified, including concerns over data privacy, limitations in technical infrastructure, and a lack of awareness of available digital health solutions. Conclusion While many patients and physicians recognize the potential of digital health technology to improve urticaria management, some remain uncertain or skeptical. Addressing concerns and improving digital understanding is critical to the future implementation and integration of these technologies into care. Due to the cross-sectional design of the study and the self-reported data, further research may be needed to confirm these results.